2018
DOI: 10.1016/j.gene.2017.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the molecular organization of unusual highly scattered 5S rDNA: The case of Chariesterus armatus (Heteroptera)

Abstract: One cluster of 5S rDNA per haploid genome is the most common pattern among Heteroptera. However, in Chariesterus armatus, highly scattered signals were noticed. We isolated and characterized the entire 5S rDNA unit of C. armatus aiming to a deeper knowledge of molecular organization of the 5S rDNA among Heteroptera and to understand possible causes and consequences of 5S rDNA chromosomal spreading. For a comparative analysis, we performed the same approach in Holymenia histrio with 5S rDNA restricted to one bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…We also found that the occurrence of rDNA loci in certain sites on chromosomes are more prone to diverge in sequence between them. This was noticed for other repetitive DNAs—for example, satellite DNA in Drosophila melanogaster (Kuhn et al., 2012) and Holhymenia histrio (Heteroptera) (Bardella et al., 2020), and 5S rDNA in Chariesterus armatus (Heteroptera) (Bardella & Cabral‐de‐Mello, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…We also found that the occurrence of rDNA loci in certain sites on chromosomes are more prone to diverge in sequence between them. This was noticed for other repetitive DNAs—for example, satellite DNA in Drosophila melanogaster (Kuhn et al., 2012) and Holhymenia histrio (Heteroptera) (Bardella et al., 2020), and 5S rDNA in Chariesterus armatus (Heteroptera) (Bardella & Cabral‐de‐Mello, 2018).…”
Section: Discussionmentioning
confidence: 82%
“…At the same time, the concerted evolution is responsible for maintaining the array by the homogenization of units, and can also foster the fixation of new variants by spreading them throughout the other arrays. A mixed model of multigene family evolution as observed here for Schistocerca has been observed in fishes (Pinhal et al 2011;Cabral-de-Mello et al 2012) and other invertebrates, including grasshoppers (Freire et al 2010;Anjos et al 2015;Bardella and Cabral-de-Mello 2018).…”
Section: Mixed Model Of Concerted Evolution and Birth-and-death Evolution Of Multigene Families In Schistocercamentioning
confidence: 71%
“…Persisting copies may then suffer divergence by mutations and sub-or neofunctionalization, or pseudogenization (Hughes and Nei 1992;Nei and Rooney 2005;Eirin-Lopez et al 2012). Recent studies suggested a mixed effect of concerted and birth-and-death evolution to be involved in some multigene families dynamics (Mount et al 2007;Freire et al 2010;Pinhal et al 2011;Merlo et al 2012; Bardella and Cabral-de-Mello 2018;Zhang et al 2021).…”
mentioning
confidence: 99%